South Africa's approach to peace mission in Africa - Hlungwani, Precious Pakamile (My University, 2017)
In 2013, the South African delegation to the African Union (AU) vigorously lobbied other AU Member States to urgently establish the African Capacity for Immediate Response to Conflict (ACIRC) Brigade. South Africa argued that the continent needed a rapid deployment force to respond quickly to conflicts. Amongst others, the ACIRC will intervene in stabilisation, peace enforcement and intervention missions, the neutralisation of terrorist groups, and attacks on legitimate governments. The decision to establish the ACIRC was a response to the M23 occupation of Goma and French intervention to assist the Malian government, which was under attack from Tuareg separatists and other Islamic fundamentalist groups. Critics of the ACIRC mechanism argue that it goes against the principles of peacekeeping and is an indication that South Africa is advocating for a departure from pacifist to robust military intervention. From South Africa’s perspective, the ACIRC Brigade is intended to fill the security gap left by the African Standby Force. This research study argues that the ACIRC is not an indicator that South Africa is advocating for a departure from pacifist to robust military intervention when resolving conflict in Africa. Instead, the ACIRC mechanism, like the Force Intervention Brigade and the French army intervention in the Democratic Republic of Congo and Mali respectively, will provide the AU with a quick response mechanism for conflict. The robustness of response will be determined by the threat at the tactical level of military operation. As such, the deployment of the ACIRC Brigade will still be guided by the principles of peacekeeping as laid out in the UN Charter and Article 4(h) of the AU Constitutive Act. In this respect, post-apartheid South Africa has played a leading role in resolving conflicts in Africa. Those who subscribe to realism argue that South Africa participates in peace missions for its own self-benefit. They argue that its participation in peace missions will increase its global stature and improve its credibility in its quest to become a permanent member of the United Nations Security Council. On the other hand, idealists argue that South Africa’s participation in peace missions is inspired by the principles of ubuntu and altruism. This research study argues that both the realist and the idealist arguments are credible when assessing South Africa’s participation in peace missions in Africa. However, Precious Pakamile Hlungwani 775032 iii notwithstanding the credibility of both arguments, there is more evidence to support the realist view on South Africa’s participation in peace missions.
A research report submitted to the Faculty of Commerce, Law and Management, in partial fulfilment of the requirements for the degree of Master of Management in Security, University of the Witwatersrand, Johannesburg, 2017
Keywords: Peace-building--Africa; Peacekeeping forces--Africa; Africa--Foreign relations